Mitigation of Make Span Time in Job Shop Scheduling Problem Using Gannet Optimization Algorithm - K. R, Anil Kumar; J., Edwin Raja Dhas (EAI endorsed transactions on scalable information systems, 2023)
INTRODUCTION: Effective (JSS) was required in the manufacturing industry to satisfy demand productivity, reduce production costs, and increase competitiveness in a market that was becoming more active and demanding of a variety of goods.OBJECTIVES: The (JSSP) has gained importance in recent years as a result of rising customer demand across a variety of categories, shifting markets due to increased global competition, and the quick development of new technology. The proper scheduling and sequencing of jobs on machines was one of the fundamental and important issues that a shop or factory management faces.METHODS: Different machines can be found in a shop, and depending on the task, one or more of these equipment may need to be used in a particular order. The aim in correcting this issue might be to reduce the make span. For each machine, the jobs sequencing must be done once the make span had been reduced.RESULTS: To solve these issues, (GOA) was used to reduce make span time. Both jobs and machines were fed as an input to the proposed optimization and to found optimal job scheduling with low make span time. The outcome of the proposed work was compared the outcomes of various optimization strategies in JSSP in order to minimize the make span time. CONCLUSION:  The objective of optimization was to reduce the total amount of time or duration required to complete a task.  A proposed gannet optimization method was employed to reduce the make span time in various sectors to resolve the job shop scheduling problem.